Australia in the Global Economy : Continuity and Change - Dyster, Barrie, 1940-; Meredith, David, 1949- (Cambridge : Cambridge University Press, 2012)
With the global economy in crisis, there is great need for a deeper understanding of Australia's economic place in the world, both today and throughout history. This new edition of Barrie Dyster and David Meredith's highly successful book is fully updated and includes three new chapters covering until the end of 2011. The book explores the evolution of Australia's position in the global economy from the start of the twentieth century through to the present day, examining the international and local economies of five key historical periods. With a focus on trade, foreign investment and immigration, the book considers periods both of growth and decline. By using historical perspectives to explain the present and give direction to the future, this unique book presents a rich account of Australia's position within a global economic context. It is an essential resource for students and lecturers of Australian economic history.
Title from publisher's bibliographic system (viewed on 01 Feb 2016).
Keywords: Australia -- Economic conditions; Australia -- Foreign economic relations